Sustainable Architectural Design Under the Effect of Global Warming - Nihal Zengin; Ruşen Yamaçlı (Doğal Afetler ve Çevre Dergisi)
Urbanization is increasing under the influence of many factors and the need for shelter cannot be met. The resulting building stock causes agglomeration in urban areas. Climate change caused by urban agglomeration leads to global temperature change. Temperature increases are experienced by urbanization, which produces latent heat. With global warming comes climate change. In the changing climate, the present and future thermal performances of buildings should be considered in the architectural design process. Sustainable architectural design, planning and material selection will ensure that the CO2 emission rate of the building sector, which plays an active role in global warming, will change positively by using existing resources effectively and efficiently by considering future generations. In this research article, answers are sought to the questions of what kind of a process architectural design should be under the influence of global warming and how the sustainability of the design can be ensured. For this reason, by proposing Biophilic Design, it has been determined that the need for air conditioning and energy consumption will decrease, and thus more sustainable cities will emerge by reducing greenhouse gas and gaseous reactive nitrogen compounds emissions. As a result of this study, the importance of emergency action plans and long-term strategies for climate problems along with a sustainable architectural design model is revealed.